2011
DOI: 10.1111/j.1365-2478.2011.00951.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical compaction and ultrasonic velocity of sands with different texture and mineralogical composition

Abstract: A B S T R A C TThis study presents the results of experimental compaction while measuring ultrasonic velocities of sands with different grain size, shape, sorting and mineralogy. Uniaxial mechanical compaction tests up to a maximum of 50 MPa effective stress were performed on 29 dry sand aggregates derived from eight different sands to measure the rock properties.A good agreement was found between the Gassmann saturated bulk moduli of dry and brine saturated tests of selected sands. Sand samples with poor sort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 31 publications
4
51
1
Order By: Relevance
“…The initial porosity is affected not only by grain size, sorting, sphericity, roundness, and filling of sediment, but it also involves grain assemblage and consolidation (He et al 2002). The initial porosity can be obtained through direct experimental measurements (Atkins and McBride 1992;Beard and Weyl 1973;Pryor 1973) or numerical simulations (Zaimy and Rasaei 2013;Fawad et al 2011;Alberts and Weltje 2001;Harbaugh et al 1999;Syvitski and Bahr 2001); however, this is a time-consuming process. In industrial practice, He et al (2002) proposed a method in which the initial porosity is assigned to fall within a reasonable range of values.…”
Section: Calculation Of Initial Porositymentioning
confidence: 99%
“…The initial porosity is affected not only by grain size, sorting, sphericity, roundness, and filling of sediment, but it also involves grain assemblage and consolidation (He et al 2002). The initial porosity can be obtained through direct experimental measurements (Atkins and McBride 1992;Beard and Weyl 1973;Pryor 1973) or numerical simulations (Zaimy and Rasaei 2013;Fawad et al 2011;Alberts and Weltje 2001;Harbaugh et al 1999;Syvitski and Bahr 2001); however, this is a time-consuming process. In industrial practice, He et al (2002) proposed a method in which the initial porosity is assigned to fall within a reasonable range of values.…”
Section: Calculation Of Initial Porositymentioning
confidence: 99%
“…In this secondary compaction phase, the relative motion between particles is very high and particle packing is thereby enhanced [12]. For the compaction processes studied in this paper, the critical stress under different operational conditions of compaction is of interest.…”
Section: Introductionmentioning
confidence: 99%
“…However, the influence of the physical characteristics of the granular geological materials is also very important. Although it has been reported that particle mineralogy and shape both affect the performance of an ultrasonic compaction 3 process [12,13], the influence of geological materials is unclear. There has been conflicting evidence between different studies with respect to the influence of vibrations on densification [14], and it has been proposed that significant differences between the physical properties of the particles, such as grain size and density, are contributory factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jenkins et al (2005) presented a combination of Walton rough and smooth model to get the effective moduli of a granular pack that has a mixture of rough and smooth surface grains. A compilation of effective granular medium models from different studies can be found at Wang and Nur (1992) and Mavko et al (2009). Fawad et al (2011 experimented on some samples of different textures (grain size, shape, sorting and mineralogy) of the granular packs and found noticeable correlation between texture and ultrasonic velocities.…”
Section: Introductionmentioning
confidence: 99%